Ultrasmall superparamagnetic iron oxide nanoparticles acutely promote thrombosis and cardiac oxidative stress and DNA damage in mice. Issue 1 (December 2015) - Nemmar, Abderrahim; Beegam, Sumaya; Yuvaraju, Priya; Yasin, Javed; Tariq, Saeed; Attoub, Samir; Ali, Badreldin
Abstract Background Ultrasmall superparamagnetic iron oxide nanoparticles (USPIO) are being developed for several biomedical applications including drug delivery and imaging. However, little is known about their possible adverse effects on thrombosis and cardiac oxidative and DNA damage. Methods Presently, we investigated the acute (1 h) effect of intravenously (i.v.) administered USPIO in mice (0.4, 2 and 10 μg/kg). Diesel exhaust particles (DEP; 400 μg/kg) were used as positive control. Results USPIO induced a prothrombotic effect in pial arterioles and venules in vivo and increased the plasma plasminogen activator inhibitor-1 (PAI-1). Both thrombogenicity and PAI-1 concentration were increased by DEP. The direct addition of USPIO (0.008, 0.04 and 0.2 μg/ml) to untreated mouse blood dose-dependently induced in vitro platelet aggregation. USPIO caused a shortening of activated partial thromboplastin time (aPTT) and prothrombin time (PT). Similarly, DEP administration (1 μg/ml) triggered platelet aggregation in vitro in whole blood. DEP also reduced PT and aPTT. The plasma levels of creatine phosphokinase-MB isoenzyme (CK-MB), lactate dehydrogenase (LDH) and troponin-I were increased by USPIO. DEP induced a significant increase of CK-MB, LDH and troponin I levels in plasma. The cardiac levels of markers of oxidative stress including lipid peroxidation, reactive oxygen species and superoxide dismutase activity were increased by USPIO. Moreover, USPIO caused DNA damage in the heart. Likewise, DEP increased the markers of oxidative stress and induced DNA damage in the heart. Conclusion We conclude that acute i.v. administration of USPIO caused thrombosis and cardiac oxidative stress and DNA damage. These findings provide novel insight into the pathophysiological effects of USPIO on cardiovascular homeostasis, and highlight the need for a thorough evaluation of their toxicity.